DEVELOPMENT OF SOLUTIONS FOR RECONSTRUCTION, DEVELOPMENT AND INTEGRATION OF TRANSPORT PRODUCTION FACILITIES - Malkov, M. I.; Radkevych, A. V.; Pavlov, I. D.; Pavlov, F. I. (Science and Transport Progress, 2005)
The paper examines a conceptual approach to the integration of production with account of intra-system links.